PENGUKURAN PENGARUH VARIABEL MOTIVASI MASLOW TERHADAP PRODUKTIVITAS TENAGA KERJA LANGSUNG DI PT SMII - Hartono, Gunawarman; R., Ratih Novalistya (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
The article purposes is to know the influence of motivation variable that consist of physiology need, safety and secure working need, social need, reward need, and actualisation need on employee productivity of home industry in Sidoarjo. Beside that, also want to know which variable has the strong influence or dominant on employee productivity. From partial or simultant test, physiology need has the strongest influence among others. That is suitable with the income level of the worker that it is only able to use for primary need.